"I found what I needed, which was a supportive community": an ethnographic study of shared information practices in an online cosplay community. Issue 3 (13th August 2021) - Vardell, Emily; Wang, Ting; Thomas, Paul A.
Abstract : Purpose: This study explored the information practices of cosplayers, as well as the social norms, social types and information infrastructure of an online cosplay Facebook group, the Rey Cosplay Community (RCC). Design/methodology/approach: To better understand individual behavior, the authors made use of ethnographic methods and semi-structured interviews. Observation of the RCC was combined with information gleaned from select participant interviews. Findings: The results suggest that the RCC can be conceived of as an information community where fans obtain and share information about cosplay costume making. Sufficient and well-organized information and positive community culture greatly help community members make their costumes. Originality/value: This works serves as a bridge between fan studies and information science research in its exploration of online communities, shared information practices and creating non-toxic virtual environments. It also lends support to the idea that positivity, respect for community rules and a tight-knit connection between members play essential roles in building a non-toxic fan and information community.